Sanctions for Inheritance Embezzlement in Indonesia: Analysis of Qiyas and Maslahah - Dulfikar, Akhmad; Syarjaya, Syibli; Somawinata, Yusuf; Tarihoran, Nafan; Syafuri, B. (Jurnal Hukum Islam, 2025)
Although embezzlement of inheritance property often occurs in Indonesia, Islamic law does not regulate sanctions for embezzlement of inheritance rights, including the Compilation of Islamic Law as the basis for Islamic inheritance law. This study examines the sanctions for embezzlement of inheritance property in Islamic law and how they are applied in Indonesia; it adopts the normative juridical method with statutory, conceptual, and case approaches. The study findings show that in classical fiqh, there are no sanctions for embezzlement of inherited property. However, based on qiyas and mashlahat mursalah, sanctions against embezzlement of inheritance property in Islamic law are in the form of moral sanctions (gibah) and takzir, whose levels are left to the imam and mujtahid. In Indonesia, a case of embezzlement of inheritance property is included in a criminal case. The sanction for this is imprisonment for a maximum of 4 years or a maximum fine of 900 rupiah as laid down in Article 372 of the Criminal Code. The author argues that the criminal sanction based on qiyas is a takzir sanction set by the government. This study offers an integrative normative framework between classical inheritance fiqh and contemporary positive law and provides a clear legal understanding for the protection of inheritance rights.